2020
DOI: 10.1002/mgg3.1317
|View full text |Cite
|
Sign up to set email alerts
|

A TOMM40/APOE allele encoding APOE‐E3 predicts high likelihood of late‐onset Alzheimer’s disease in autopsy cases

Abstract: Background The APOE ‐ε4 allele is an established risk factor for Alzheimer's disease (AD). TOMM40 located adjacent to APOE has also been implicated in AD but reports of TOMM40 associations with AD that are independent of APOE ‐ε4 are at variance. Methods We investigated associations of AD with haplotypes defined by three TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 108 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…TOMM40 encodes the mitochondrial protein import channel, and is indispensable for maintaining mitochondrial homeostasis ( Baker et al, 1990 ; Taylor et al, 2003 ) and for life ( Zeh, 2013 ). Multiple SNPs in TOMM40 are associated with AD risk independently of the APOE gene., including rs7259620 ( Takei et al, 2009 ; Nazarian et al, 2019 ), rs760136 ( Marioni et al, 2018 ), rs2075650 ( He et al, 2016 ; Huang et al, 2016 ; Bussies et al, 2020 ; Soyal et al, 2020 ; Squillario et al, 2020 ), and rs10524523 ( Roses, 2010 ; Li et al, 2013 ; Yu et al, 2017a , b ). Both APOC1 and PVRL2 fit the pattern of being lipid- or immune-related.…”
Section: Pparγ and Ad-related Risk Factorsmentioning
confidence: 99%
“…TOMM40 encodes the mitochondrial protein import channel, and is indispensable for maintaining mitochondrial homeostasis ( Baker et al, 1990 ; Taylor et al, 2003 ) and for life ( Zeh, 2013 ). Multiple SNPs in TOMM40 are associated with AD risk independently of the APOE gene., including rs7259620 ( Takei et al, 2009 ; Nazarian et al, 2019 ), rs760136 ( Marioni et al, 2018 ), rs2075650 ( He et al, 2016 ; Huang et al, 2016 ; Bussies et al, 2020 ; Soyal et al, 2020 ; Squillario et al, 2020 ), and rs10524523 ( Roses, 2010 ; Li et al, 2013 ; Yu et al, 2017a , b ). Both APOC1 and PVRL2 fit the pattern of being lipid- or immune-related.…”
Section: Pparγ and Ad-related Risk Factorsmentioning
confidence: 99%
“…However, more recent results based on gene haplotypes have shown a strong influence of the regulated expression of the gene in the brain [ 79 ]. Similarly, several association studies have shown mixed results regarding the association of TOMM40 (outer mitochondrial membrane translocase 40) with AD and the dysregulation of mitochondrial function independent of ApoE4 [ 80 , 81 ], but a recent haplotype study showed differences between TOMM40 haplotypes encoding ApoE4 and ApoE3 in the association probability for AD [ 82 ].…”
Section: The Genetics Of Admentioning
confidence: 99%
“…However, this does not explain why APOE and TOMM40 are independently linked to age of onset distributions for Alzheimer’s disease 15 , and why in individuals homozygous for APOE ε3 ( i.e. null for the ε4 allele), distinct TOMM40 variants differentially increase disease risk and age of onset 16 , 17 . There is a growing appreciation that upregulated TOMM40 gene expression due to TOMM40 polymorphisms is sufficient to predispose individuals to Alzheimer’s disease 16 , 18 – 21 , and an emerging school of thought endorses TOMM40 as an independent genetic determinant of Alzheimer’s pathology 22 , 23 .…”
Section: Introductionmentioning
confidence: 97%